2011
DOI: 10.1007/s10461-011-9971-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Antiretroviral Therapy in the Swiss HIV Cohort Study: Latent Class Analysis

Abstract: An in-depth understanding of the different groups that make up the HIV-infected population should inform prevention and care. Using latent class analysis (LCA) we identified seven groups with similar sociodemographic and behavioral characteristics at enrolment in the Swiss HIV Cohort Study: older gay men, younger gay men, older heterosexual men, injection drug users, single migrants, migrant women in partnerships and heterosexual men and women. Outcomes of combination antiretroviral therapy (ART) were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…This result is important itself, especially in the light of the contemporary studies on aforementioned topic, which were mainly concerned with identifying single sociomedical and/or psychological variables that are independently associated with various aspects of PWB in this patient group (Degroote et al 2014). Keiser et al (2012) in one of the few studies using latent profile analysis among PLWH suggested that a possible reason for many conflicting results in the literature on the PWB among PLWH is the fact that the majority of authors neglected how particular socio-medical and psychosocial variables may cluster across different HIV+ patients groups distinguished on the basis of various levels of PWB, which may be influenced by a variety of factors simultaneously. This study addressed the gap in the literature by examining sociomedical and personality covariates after identifying groups of PLWH that are similar with regard to different domains of PWB.…”
Section: Discussionmentioning
confidence: 98%
“…This result is important itself, especially in the light of the contemporary studies on aforementioned topic, which were mainly concerned with identifying single sociomedical and/or psychological variables that are independently associated with various aspects of PWB in this patient group (Degroote et al 2014). Keiser et al (2012) in one of the few studies using latent profile analysis among PLWH suggested that a possible reason for many conflicting results in the literature on the PWB among PLWH is the fact that the majority of authors neglected how particular socio-medical and psychosocial variables may cluster across different HIV+ patients groups distinguished on the basis of various levels of PWB, which may be influenced by a variety of factors simultaneously. This study addressed the gap in the literature by examining sociomedical and personality covariates after identifying groups of PLWH that are similar with regard to different domains of PWB.…”
Section: Discussionmentioning
confidence: 98%
“…Mazuecos et al (22) reported their coinfected group to have had longer dialysis and HIV disease duration prior to transplantation and a greater likelihood of drug addiction history. Other information about coinfection from the nontransplant literature indicates that HCV coinfection is associated with active drug use, lower income, less education and younger age as well as a greater likelihood of having an AIDS diagnosis at baseline, increased risks of clinical progression to an AIDS-defining event or death, lower median baseline CD4 counts and lower likelihood of CD4 count increases while on therapy (28). Taken together the available information suggests that the presence of coinfection may represent a higher-risk group either due to biological and/or behavioral risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…LCA is a statistical analysis that uncovers subgroups, or ''classes'' defined by distinct response patterns on multiple HIV risk factors. LCA has been used to evaluate substance use, [18][19][20][21][22][23] HIV risk factors, [24][25][26] medication adherence, 27 and other HIV behaviors, [28][29][30] but has not been widely used to elucidate classes of MSM who may benefit most from PrEP.…”
Section: Introductionmentioning
confidence: 99%